IMPLEMENTASI CSMS DAN FAKTOR-FAKTOR YANG MEMPENGARUHI EFEKTIFITASNYA TERHADAP KINERJA SAFETY KONTRAKTOR DI PT VALE INDONESIA - Sudirman Basri; Abdul Rahman Kadir; Fauziah Umar (Hasanuddin Journal of Applied Business and Entrepreneurship, 2019)
Safety of life and work (safety) is the main value that must be owned by every company, not least PT Vale Indonesia (PTVI) as a nickel mining and processing company operating in Sorowako, South Sulawesi. This study aims to examine the implementation and effectiveness of CSMS, including the factors that affect the safety performance of contractors at PT Vale Indonesia in Sorowako. This study was conducted by analyzing the significance and correlation between CSMS implementation and its effectiveness as well as the influencing factors: culture and behavior, work conditions, resources, communication and training. The analytical tool used is Chi Square and Kendall's Tau with primary data obtained from the questionnaire survey to the parties related to CSMS that are contractors and stakeholders in PT Vale Indonesia and secondary data in the form of data safety record in EHS department of PT Vale Indonesia. The results of this study indicate that the CSMS program in PT Vale Indonesia has been implemented well and sufficiently, so the effects of the program have been in accordance with its objectives and lead to targets determined on the quantity side, but in terms of quality needs to be improved further by increasing fulfillment of CSMS implementation and significant influencing factors are: improvement of training, communication and culture and safety behavior.